2012
DOI: 10.1353/hpu.2012.0045
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Treatment and Control of Hypertension, Diabetes and Hyperlipidemia and Area-Level Mortality Regions in the Reasons for Geographic and Racial Differences in Stroke (REGARDS) Study

Abstract: Background Health Professional Shortage Areas (HPSA) receive extra federal resources, but recent reports suggest that HPSA may not consistently identify areas of need. Purpose To assess areas of need based on county-level ischemic heart disease (IHD) and stroke mortality regions. Methods Need was defined by lack of awareness, treatment, or control of hypertension, diabetes, or hyperlipidemia. Counties were categorized into race-specific tertiles of IHD and stroke mortality using 1999–2006 CDC data. Multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Among the 1821 US counties represented in REGARDS, those in the highest tertile of CHD mortality formed a crescent-like band stretching from the Northeast towards Texas and extending into New Mexico, Southern California, and Southwestern Nevada (Table 2) [6]. REGARDS has revealed important racial and gender disparities in prevalence of CHD in the study population.…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Among the 1821 US counties represented in REGARDS, those in the highest tertile of CHD mortality formed a crescent-like band stretching from the Northeast towards Texas and extending into New Mexico, Southern California, and Southwestern Nevada (Table 2) [6]. REGARDS has revealed important racial and gender disparities in prevalence of CHD in the study population.…”
Section: Incidencementioning
confidence: 99%
“…Health Professional Shortage Areas (HPSA) are federally designated geographic regions based on population size and physician availability [34]. The HPSA designation involves a complex process that factors in the ratio of provider to patients, underserved populations or sociodemographic uniqueness, and health-care facilities that provide primary care services to a population group [6, 34]. REGARDS has shown that, while awareness of chronic conditions such as hypertension was greater among uninsured participants in HPSA compared with uninsured participants in non-HPSA, the rates of treatment were similar in both groups, but the odds of BP control were lower in the former compared with the latter [35].…”
Section: Risk Factorsmentioning
confidence: 99%
“…may also play a role in disease's prevalence 2, 37, 39-41. The nature of hypertension-related health risk is similar in all populations, but the distribution of diseases with regard to those risk factors may vary 38, 42.…”
Section: Introductionmentioning
confidence: 99%
“…Black Americans and residents of the southeastern United States, a region also known as the Stroke Belt due to elevated stroke mortality, are at greater risk of coronary heart disease (CHD) 9 mortality and fatal incident CHD than are whites and those living elsewhere (1)(2)(3). High adherence to a Southern dietary pattern, characterized by fried foods, organ meats, and sugarsweetened beverages, is more common among men, non-Hispanic blacks, and residents of the southeastern United States and has been associated with a 66% increased risk of incident CHD (4).…”
Section: Introductionmentioning
confidence: 99%